Association of comorbidities with the COVID-19 severity and hospitalization: A study among the recovered individuals in Bangladesh - Ganguli, Sumon; Howlader, Sabbir; Dey, Kamol; Barua, Suman; Islam, Md. Nazrul; Aquib, Tahmidul Islam; Partho, Prosenjit Biswas; Chakraborty, Rivu Raj; Barua, Bidduth; Hawlader, Mohammad Delwer Hossain; Biswas, Paritosh Kumar (International Journal of Health Sciences, 2022)
Objectives: We aimed at the identification of the association of comorbidities with the COVID-19 severity and hospitalization. Methods: It is a retrospective cross-sectional study to investigate the variation in age, sex, dwelling, comorbidities, and medication with the COVID-19 severity and hospitalization by enrolling 1025 recovered individuals while comparing their time of recovery with or without comorbidities. Results: COVID-19 patients mostly suffered from fever. The predominant underlying medical conditions in them were hypertension (HTN) followed by diabetes mellitus (DM). Patients with cardiovascular disease (CVD) (54.3%) and hepatic disorders (HD) (43.6%) experienced higher severity. The risk of symptomatic cases was higher in aged (odds ratio, OR = 1.04, 95% CI = 1.02–1.06) and comorbid (OR = 1.87, 95% CI = 1.34–2.60) patients. T-test confirmed the differences between the comorbid and non-comorbid patients’ recovery duration. The presence of multiple comorbidities increased the time of recovery (15–27 days) and hospitalization (20–40%). Increased symptomatic cases were found for patients having DM+HTN whereas CVD+Asthma patients were found with higher percentage of severity. Besides, DM+CKD (chronic kidney disease) was associated with higher hospitalization rate. Higher odds of severity were found for DM+CVD (OR = 4.42, 95% CI = 1.81–10.78) patients. Hospitalization risk was also increased for them (OR = 5.14, 95% CI = 2.02–13.07). Moreover, if they had HTN along with DM+CVD, they were found with even higher odds (OR = 6.82, 95% CI = 2.37–19.58) for hospitalization. Conclusion: Our study indicates that people who are aged, females, living in urban area and have comorbid conditions are at a higher risk for developing COVID-19 severity. Clinicians and health management authorities should prioritize these high-risk groups to reduce mortality attributed to the disease.